ISAF 2000. Proceedings of the 2000 12th IEEE International Symposium on Applications of Ferroelectrics (IEEE Cat. No.00CH37076)
DOI: 10.1109/isaf.2000.942396
|View full text |Cite
|
Sign up to set email alerts
|

Physics based fatigue compact model for ferroelectric capacitors

Abstract: A physics based compact model describing the fatigue behavior of ferroelectric capacitors has been developed. Fatigue is a gradual decrease of detectable polarization with increasing number of polarization cycles. This can be caused by trapped charges which pin dipoles near the interface to the electrode. In order to polarize those pinned dipoles they have to be separated from the trapped charges by a higher electrical force. This force has been described in our model by additional coercive voltages representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It is shown that this assumption is not valid when the material is subjected to a ''local imprint'' phenomenon. 11 The experimental PD shown in Fig. 6͑a͒ seems to be a two-dimensional-Gaussian distribution.…”
Section: Ferroelectric Model Based On a Csdmentioning
confidence: 91%
“…It is shown that this assumption is not valid when the material is subjected to a ''local imprint'' phenomenon. 11 The experimental PD shown in Fig. 6͑a͒ seems to be a two-dimensional-Gaussian distribution.…”
Section: Ferroelectric Model Based On a Csdmentioning
confidence: 91%